Kecurangan dalam Jual Beli Menurut Al-Qur’an Perspektif Tafsir Al-Munir - Mia Dwi Setiawahyu; Yusrizal Efendi (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2022)
An honest, transparent merchant on the goods offered, does not raise the price too high on the buyer, and such a person will get a measure of blessings in the world and in the afterlife with the prophets. Yet cheating as far as buying and selling is concerned remains that merchants who expose the good and hide the defective, which can bring mudharats to any item sold of a different quality, of course a Muslim would know that such acts are prohibited by the religion. The purpose of this study is: (1) to describe and analyze forms of cheating in the phrasing of al-munir and (2) to describe and analyze the impact it would have on people in al-munir's interpretation. The type of research that the author uses is research library (library research) by means of thematic or maudhu'i interpretation analysis and the study of characters.